THE EFFECT OF THE SEARCH, SOLVE, CREATE, AND SHARE (SSCS) LEARNING MODEL ON THE LEARNING OUTCOMES OF STUDENTS - Amanda, Tiara Citra (Department of Physics Universitas Negeri Padang, 2024)
This research is motivated by the low learning outcomes from physics of students caused by the models of learning utilized by teachers in schools that are less varied in related to demands of Curriculum 2013. The research purpose is to analyze the model of SSCS learning impact on learning outcomes of students'. The model of SSCS learning is a variation of a methodology that emphasizes problem-solving and has the ability to raise student achievement levels. The Randomized Posttest Only Control Group Design is a quasi-experimental methodology utilized in this research. The sample in this study consisted of 68 students through two classes for sample, known as classes for experimental and control was got by technique of purposive sampling. The instruments used in this research were valid and reliable tests. Based on the research results obtained that the price of t is outside of H0's acceptance region, allowing H1 to be accepted at a real level of 0.05. This indicates that students receiving treatment have different learning results in physics. Thus the conclussion that there is an impact of SSCS learning model on physics learning outcomes of students who are given treatment.